Influence of growth regulating chemicals on growth and flowering in Jasmine (Jasminum sambac.Ait.) - D Dhanasekaran (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2018)
Jasmine is an important commercial flower crop in Tamil Nadu. The crop has a main flowering season during March to October and an off-season from November to February. During this off-season, flowering is very poor or there is no flowering in many growing areas. In recent years, growth regulators are valuable in floriculture for manipulating growth and flowering of many crops and hence and attempt has been made to induce flowering during off season using growth regulators in Jasmine in the Floriculture unit of the Department of Horticulture, Faculty of Agriculture, Annamalai University, Tamil Nadu during November, 2016 to February, 2017. The treatment comprises of three concentrations of each of two growth promoting substances viz., NAA and GA3 and two growth retardants (Cycocel and Maleic Hydrazide). The experiment was laid out in randomized block design with three replications. Among the various treatments, application of NAA @ 75 ppm (T6) recorded the highest plant height (130.6 cm and 178.5 cm at 90 and 180 DAP respectively), number of primary shoots (21.68 and 35.68 at 90 and 180 DAP respectively), number of nodes (9.86 and 15.89 cm at 90 and 180 DAP respectively) and number of leaves (1250.0 and 2689.5 at 90 and 180 DAP respectively). Earliness in flowering (26.38 DAP) and maximum duration of flowering (171.00 days) was noticed in (GA3@ 150 ppm T3). From the above studies, it is inferred that application of GA3 @ 150 ppm could be recommended for enhanced growth and higher flower yield in Jasminum sambac.